Evidence for photochemical transformations in porous silicon - Shevchenko, V.B.; Makara, V.A.; Vakulenko, O.V.; Dacenko, O.I.; Rudenko, O.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 1999)
The dynamics of the variation of photoluminescence intensity (PLI) of porous silicon (PS) samples subjected to laser irradiation (337 nm, 3.7 mW) during their ageing in air has been studied. The PLI turned out to increase rapidly under UV irradiation and to flatten out in several hours. The subsequent irradiation leads to intensity degradation, which may be explained by the luminescence fatigue effect. At the same time, the PLI of the unilluminated sample almost does not change during the experiment. It turned out that the anomaly as a small surge down is observed on the PLI evolution curve at the stage of the initial monotonous increase of PLI after a short-time (1 to 2 minutes) interruption of the laser illumination of the sample, whereas this anomaly is a surge up at the stage of the monotonous fall of the PLI curve. In the case of a long-time (tens of hours) discontinuation of illumination, the anomaly was similar for all the portions of the PLI curve. The described results are explained by effect of two competing factors which are the luminescence fatigue and light-induced formation of unstable (molecular) chemical bonds that can transform to the stable atomic ones.